2020
DOI: 10.14814/phy2.14347
|View full text |Cite
|
Sign up to set email alerts
|

The left ventricle undergoes biomechanical and gene expression changes in response to increased right ventricular pressure overload

Abstract: Pulmonary hypertension (PH) results in right ventricular (RV) pressure overload and eventual failure. Current research efforts have focused on the RV while overlooking the left ventricle (LV), which is responsible for mechanically assisting the RV during contraction. The objective of this study is to evaluate the biomechanical and gene expression changes occurring in the LV due to RV pressure overload in a mouse model. Nine male mice were divided into two groups: (a) pulmonary arterial banding (PAB, N = 4) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Isolated RV pressure overload in a PAB model resulted in reduced LV ejection fraction and stroke work, as well as LV atrophy (reduced wall thickness) (Kheyfets et al, 2020). Since the total work performed by LV contraction is shared between displacing blood within the systemic circulation and supporting RV contractions, reduced LV stroke work in this PAB model was attributed to the increased demand of the RV (Kheyfets et al, 2020), leading to less work being allocated to the systemic circulation. PAH induced in rats via MCT resulted in decreased LV and systemic pressures, and reduced LV dp dt max and dp dt min , measured in vivo (Han et al, 2018).…”
Section: Effects Of Pah On Left Ventricular Organ-level Mechanicsmentioning
confidence: 86%
See 2 more Smart Citations
“…Isolated RV pressure overload in a PAB model resulted in reduced LV ejection fraction and stroke work, as well as LV atrophy (reduced wall thickness) (Kheyfets et al, 2020). Since the total work performed by LV contraction is shared between displacing blood within the systemic circulation and supporting RV contractions, reduced LV stroke work in this PAB model was attributed to the increased demand of the RV (Kheyfets et al, 2020), leading to less work being allocated to the systemic circulation. PAH induced in rats via MCT resulted in decreased LV and systemic pressures, and reduced LV dp dt max and dp dt min , measured in vivo (Han et al, 2018).…”
Section: Effects Of Pah On Left Ventricular Organ-level Mechanicsmentioning
confidence: 86%
“…Pulmonary arterial hypertension primarily affects RV structure and function; however, RV and LV function are interdependent on one other and LV contraction assists with 20-40% of the systolic RV pressure rise (Santamore and Dell'Italia, 1998). Alterations in RV structure/function such as RV dilation and impaired contractility directly affect the organ-level biomechanics of the LV by reducing LV torsion and resulting in delayed peak torsion (Kaiser et al, 2020;Kheyfets et al, 2020). Isolated RV pressure overload in a PAB model resulted in reduced LV ejection fraction and stroke work, as well as LV atrophy (reduced wall thickness) (Kheyfets et al, 2020).…”
Section: Effects Of Pah On Left Ventricular Organ-level Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies show that RV free wall remodeling -commonly seen under pressure overload—can mechanically decrease LV torsion [ 31 , 43 ]. It has also been demonstrated that this decrease in LV torsion and torsion rate occurs within the first week of PAB in mice [ 31 ], which would further suggest that the effect is biomechanical stimuli from the remodeling and pressure overloaded RV free wall or septum. However, to our knowledge, there is no direct evidence to mechanistically link decreased LV torsion rate to decreased RV contractility in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…The third includes additional information on the LV obtained by echocardiography (23). Finally, the fourth experimental design represents a realistic, but underutilized, scenario that includes pressure-volume measurements in both the RV and LV (11,26). We perform all sensitivity and identifiability analyses with respect to the pressure and volume forecasts considered in the four experimental designs above.…”
Section: Simulated Experiments and Additional Outputsmentioning
confidence: 99%